2016
DOI: 10.1021/acs.cgd.6b00205
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Cyclic Fluoride–Water and Sulfate–Water–Sulfate Cluster Within the Self-Assembled Structure of Linear meta-Phenylenediamine Based Bis-Urea Receptors: Positional Isomeric Effect

Abstract: meta-Phenylenediamine based two linear bis-urea anion receptors, L 1 (meta-nitro) and L 2 (para-nitro), have been synthesized which showed strong binding affinities toward halides as well as planar and tetrahedral oxyanions. In the presence of excess fluoride anion, L 1 self-assembles to entrap a cyclic fluoride–water tetrameric cluster within its tetrameric pillar-like assembly of each urea arm (complex 1a). In the presence of sulfate anion, L 1 self-assembles in an identical fashion to entrap the big… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…Pores formed via the assembly of two or more functional building units are commonly used to capture specific anions. 3537 Example include a fluoride anion dimer and a sulfate anion dimer stabilized by the isomeric meta -phenylene based bis-urea receptors 19 ( meta -nitro) and 20 ( para -nitro), respectively, as reported by Manna et al 38 Although both receptors favor a linear conformation, they proved capable of interacting with halide anions as well as planar and tetrahedral oxyanions. In the case of receptor 19 , a single crystal X-ray crystallographic analysis revealed that the four urea arms derived from four different molecules of 19 assemble into a barrel-like structure that acts to entrap a fluoride dimer bridged by two water molecules.…”
Section: Acyclic Anion Receptorsmentioning
confidence: 88%
“…Pores formed via the assembly of two or more functional building units are commonly used to capture specific anions. 3537 Example include a fluoride anion dimer and a sulfate anion dimer stabilized by the isomeric meta -phenylene based bis-urea receptors 19 ( meta -nitro) and 20 ( para -nitro), respectively, as reported by Manna et al 38 Although both receptors favor a linear conformation, they proved capable of interacting with halide anions as well as planar and tetrahedral oxyanions. In the case of receptor 19 , a single crystal X-ray crystallographic analysis revealed that the four urea arms derived from four different molecules of 19 assemble into a barrel-like structure that acts to entrap a fluoride dimer bridged by two water molecules.…”
Section: Acyclic Anion Receptorsmentioning
confidence: 88%
“…It is now documented that a urea or thiourea group is capable to chelate an anion via two directional H-bonds (Jia et al, 2016). Therefore, the molecules containing (thio)urea moieties with flexible (Nishizawa et al, 1995;Nishizawa et al, 1998;Emgenbroich et al, 2008;Duke et al, 2012;Caltagirone et al, 2013;Olivari et al, 2015;Gillen et al, 2018) or rigid (Manna et al, 2016;Khansari et al, 2017b;Gale and Gunnlaugsson, 2010) linkers have been successfully applied as a promising class of receptors for anion recognition purpose in recent past years. Nishizawa et al (1995) reported bis(thio)urea receptors containing n-butyl terminals with a flexible metaxylylenediamine-based linker, exhibiting preferable binding for H 2 PO 4 − and SO 4 2− over other anions as evaluated by NMR studies.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported allosteric effects in the binding of several anions to a series of acetamido-substituted diphenylureas and thioureas, due to the presence of the additional hydrogen bonding group adjacent to the urea. , Similar effects in symmetric phenylene bisureas have been noted: ortho -phenylene bisureas have been established by Gale and co-workers as excellent hydrogen bonding receptors for carboxylate anions and tetrahedral oxoanions due to the four convergent hydrogen bonds, while the bis­(urea)–carboxylate interaction displayed by these has been utilized as a supramolecular synthon . Wu and co-workers have used bis­(biurea) derivatives to form both PO 4 3– templated helicates and cages, while Das and co-workers have developed several electron-poor meta -phenylene bis­(phenyl­urea) receptors, and studied their interactions with anions, with an emphasis on their crystalline adducts. Others have extended the aromatic moieties of this framework: Ghosh et al developed a series of coumarin-containing receptors and studied their interactions with mono- and dicarboxylate anions, while the group of Caltagirone found that pyrophosphate binding in phenylene bis­(aryl­urea) systems is promoted in asymmetric hosts bearing a naphthalene and an indole ring …”
Section: Introductionmentioning
confidence: 81%